(untitled) (Journal of the Bangladesh Agricultural University, 2014)
The experiment was conducted to study the performance of Kukje self-propelled rice transplanter and to study the economic feasibility of mechanical transplanting method over manual transplanting method. Each of the transplanting method had three unit plots of sized 20 m x 10 m. The field efficiency and planting efficiency of the transplanter were 83.33% and 95%, respectively. Percent damaged (3.33%) and missing (5.33%) hills were higher in mechanical transplanting method and percent floating (4.33%) hill was higher in case of manual transplanting method. The average labor input in mechanical transplanting was 1.4 man-day/ha where 25 man-day/ha was in case of manual transplanting. The total production costs were 53612 tk/ha and 49304 tk/ha for manual transplanting and mechanical transplanting methods, respectively. Crop established with mechanical transplanting method resulted in higher average grain yield of 6.66 t/ha than manual transplanting method resulted average grain yield of 5.83 t/ha. The net return of manual and mechanical transplanting method were 42310 and 61080 tk/ha, respectively. The benefit cost ratios (BCR) were 2.24 and 1.78 for mechanical transplanting method and manual transplanting method, respectively. Kukje self-propelled rice transplanter should have break-even area coverage more than 10 ha/yr for economic transplanting. The above result showed that the mechanical transplanting method is more economic than the manual transplanting method. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21406 J. Bangladesh Agril. Univ. 12(1): 161-166, June 2014